Traditional and Religious Beliefs on Mental Illness and Help-Seeking Behaviour in Ife Central LGA, Ogun State - Shipurut, Geoffrey Nanbal (Darul Yasin Al Sys, 2024)
Traditional and religious beliefs are essential in mental health discourse and help-seeking behaviour. The study explored the impact of traditional and religious beliefs on mental illness and help-seeking behaviour, in Ife Central LGA. The Health Belief Model (HBM) was adopted as the theoretical framework for the study. The study used a phenomenology research design. Qualitative data was collected from 12 key informants who were purposely selected for the study. The data was analyzed while outlining the key point presented by the key informant. The study revealed that stigma and discrimination are often associated with mental illness and help-seeking behaviour in Ife Central LGA. Mental illness is widely stigmatized and misunderstood. The study also revealed that perceived causes of mental illness include drug abuse, possession by evil spirits, inherited through the family, and punishment from God. The study concluded that misconceptions about the causes of mental illness might consequently lead to misconceptions about treatment. Religious and traditional beliefs in supernatural causes and remedies of mental illnesses influence people’s knowledge and attitudes towards mental illness and help-seeking behaviour. The study recommends the decentralization of mental health care services from urban areas down to rural health centres where mental health services can be rendered with psychiatric services as well. There is a need for community education of the people on the causes of mental illness. It is due to ignorance that most people wrongly believe that mental illness must have some spiritual undertone.